Komunitas SLiMS Semarang sebagai ruang inovasi pustakawan - Mochammad Riski Destrianto; Heriyanto Heriyanto (Jurnal Kajian Informasi dan Perpustakaan, 2020)
Senayan Library Management System (SLiMS) software formed by SLiMS developers in 2008. Members of the SLiMS Community are librarians who play an important role in making innovations from interactions in an exchange of knowledge and produce various works. This study aimed to identify the Semarang SLiMS Community as a space for librarians' innovation in developing their competence. The method used is qualitative with a case study approach. Collecting data techniques was carried out using semi-structured interviews with four informants. The collected data was then analyzed using thematic analysis. Analysis results showed that the SLiMS Community was a space for librarians to improve their competence, especially in the field of SLiMS development. The patterns identified included motivation, knowledge sharing, collaboration, and innovation. Motivational factors included the desire to share knowledge, increase competence, and raise professional degrees to job demands. The second stage is knowledge sharing, conducted using ‘Sinau Bareng’, ‘Library Clinic’, workshops, and others. The third stage of collaboration is the interaction of community members with other communities to produce innovations. The last stage is innovation, describing outputs or achievements such as products, ideas, and new activities. Innovation is the beginning of the formation of new knowledge. This study concludes that the Semarang SLiMS Community can generate knowledge cycles that lead to innovation.